Considerations in Addressing Social Determinants of Health to Reduce Racial/Ethnic Disparities in Stroke Outcomes in the United States. Issue 11 (November 2020) - Skolarus, Lesli E.; Sharrief, Anjail; Gardener, Hannah; Jenkins, Carolyn; Boden-Albala, Bernadette
Abstract : We write this article amid a global pandemic and a heightened awareness of the underlying structural racism in the United States, unmasked by the recent killing of George Floyd and multiple other unarmed Black Americans (Spring 2020). Our purpose is to highlight the role of social determinants of health (SDOH) on stroke disparities, to inspire dialogue, to encourage research to deepen our understanding of the mechanism by which SDOH impact stroke outcomes, and to develop strategies to address SDOH and reduce stroke racial/ethnic disparities. We begin by defining SDOH and health disparities in today's context; we then move to discussing SDOH and stroke, particularly secondary stroke prevention, and conclude with possible approaches to addressing SDOH and reducing stroke disparities. These approaches include (1) building on prior work; (2) enhancing our understanding of populations and subpopulations, including intersectionality, of people who experience stroke disparities; (3) prioritizing populations and points along the stroke care continuum when racial/ethnic disparities are most prominent; (4) understanding how SDOH impact stroke disparities in order to test SDOH interventions that contribute to the disparity; (5) partnering with communities; and (6) exploring technological innovations. By building on the prior work and expanding efforts to address SDOH, we believe that stroke disparities can be reduced.